Cloud Brokerage and Cost Optimization: An Empirical Study of Cloud Cost Saving - Aniket Surkunde; Diven Gardas; Krishna Dharrao; Shubham Shinde; Dr. Syed Irfan (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Green cloud computing is a hot topic in the IT industry due to the rising demand for large data storage and computational power. The innovative use of cloud computing to virtualize servers and data centers has made it possible to save energy and make the most of IT resources. Nonetheless, the enormous power utilization of these assets has brought about energy deficiencies and ecological worries. Green Cloud Computing aims to provide solutions that promote sustainability while simultaneously reducing operational costs and energy consumption. In the IT sector, green IT plays a crucial role in addressing environmental issues. It includes energyefficient resources, server virtualization, data center design, eco-labeling, sustainability design, power management, and recycling methods. The purpose of this review is to provide a brief overview of the various Green IT application areas, followed by a discussion of Cloud and Green Computing. Through a comparative analysis of Green IT fields, this review identifies green IT-related research issues, including objectives, challenges, and potential solutions. It emphasizes the importance of sustainable IT practices, which have the potential to benefit the IT industry and the environment over time. Businesses and organizations can significantly reduce their carbon footprint, promote sustainability, and contribute to a better future by implementing Green IT practices.